2017
DOI: 10.1038/ncomms14796
|View full text |Cite
|
Sign up to set email alerts
|

Complex picture for likelihood of ENSO-driven flood hazard

Abstract: El Niño and La Niña events, the extremes of ENSO climate variability, influence river flow and flooding at the global scale. Estimates of the historical probability of extreme (high or low) precipitation are used to provide vital information on the likelihood of adverse impacts during extreme ENSO events. However, the nonlinearity between precipitation and flood magnitude motivates the need for estimation of historical probabilities using analysis of hydrological data sets. Here, this analysis is undertaken us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
107
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 24 publications
7
107
0
Order By: Relevance
“…Flooding at individual stations is known to exhibit serial correlation (Douglas et al, 2000;Mallakpour et al, 2017), with flood-rich and flood-poor periods; our results show that at a larger scale, years with widespread flooding are also clustered in time. However, although flood risks in Europe are known to be affected by the El Niño-Southern Oscillation and the North Atlantic Oscillation (Emerton et al, 2017;Nobre et al, 2017;Ward et al, 2014), neither has a measurable correlation with the average European flood synchrony scale ( Figure S5). However, although flood risks in Europe are known to be affected by the El Niño-Southern Oscillation and the North Atlantic Oscillation (Emerton et al, 2017;Nobre et al, 2017;Ward et al, 2014), neither has a measurable correlation with the average European flood synchrony scale ( Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…Flooding at individual stations is known to exhibit serial correlation (Douglas et al, 2000;Mallakpour et al, 2017), with flood-rich and flood-poor periods; our results show that at a larger scale, years with widespread flooding are also clustered in time. However, although flood risks in Europe are known to be affected by the El Niño-Southern Oscillation and the North Atlantic Oscillation (Emerton et al, 2017;Nobre et al, 2017;Ward et al, 2014), neither has a measurable correlation with the average European flood synchrony scale ( Figure S5). However, although flood risks in Europe are known to be affected by the El Niño-Southern Oscillation and the North Atlantic Oscillation (Emerton et al, 2017;Nobre et al, 2017;Ward et al, 2014), neither has a measurable correlation with the average European flood synchrony scale ( Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…Given the low correlations we have found here between floodiness and either seasonal total rainfall or other rainfall indicators, forecasts of any of these proxies are unlikely to provide strong signals of increased risk. However, there have been several studies using large-scale climate patterns and sea surface temperatures (SSTs) as predictors of flood risk, most focusing on the role of ENSO in changing global flood risk (Emerton et al, 2017;Ward et al, 2014Ward et al, , 2016. Further research on using SSTs and other climate patterns to directly forecast changes to flooding is merited, to explore whether such forecasts would give stronger indications of change in flood hazard than seasonal climate models of rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…Together, we can see that the monotonic trend initially observed in the frequency of floods at the global and the sub-spatial scales may be due to the variability in the climate and atmospheric teleconnections. Ward et al (2016) and Emerton et al (2017) have previously demonstrated the role of ENSO in modulating global floods. In addition, Hodgkins et al (2017) demonstrated recently that AMO has a significant negative (positive) relationship with 25-and 50-year flood occurrence for large (medium) catchments in North America (Europe).…”
Section: Millionsmentioning
confidence: 99%